2011
DOI: 10.1007/s13353-011-0068-7
|View full text |Cite
|
Sign up to set email alerts
|

Current genetic methodologies in the identification of disaster victims and in forensic analysis

Abstract: This review presents the basic problems and currently available molecular techniques used for genetic profiling in disaster victim identification (DVI). The environmental conditions of a mass disaster often result in severe fragmentation, decomposition and intermixing of the remains of victims. In such cases, traditional identification based on the anthropological and physical characteristics of the victims is frequently inconclusive. This is the reason why DNA profiling became the gold standard for victim ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
90
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 147 publications
0
90
0
1
Order By: Relevance
“…For example, prolonged exposure of even a large blood stain to the environment can degrade the DNA and make it unsuitable for further analysis (7). Environmental sources of degradation are chemical (acids, bases, strong oxidizing agents), physical (heat and sunlight) and biological (bacteria and fungi) (1,3). The most common source of degradation is biological in the form of mold and mildew.…”
Section: Degradationmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, prolonged exposure of even a large blood stain to the environment can degrade the DNA and make it unsuitable for further analysis (7). Environmental sources of degradation are chemical (acids, bases, strong oxidizing agents), physical (heat and sunlight) and biological (bacteria and fungi) (1,3). The most common source of degradation is biological in the form of mold and mildew.…”
Section: Degradationmentioning
confidence: 99%
“…In comparison to soft tissues, hard tissues are greatly resistant to autolysis and decomposition caused by environmental factors. Therefore, bones, teeth and nails are the only source of DNA in some forensic cases (3,29). Miloš et al have shown that femur provided the best success rates while clavicle, ulna, and radius provided the lowest success rates (23).…”
Section: Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…These devices combined with analysis of short tandem repeats (STRs) will improve both forensic human identification and medical diagnostics, in particular genetic alteration linked with mutation in STR regions [1][2][3] in terms of speed, cost, and accuracy of the results. Modern STR analysis systems 4,5 are based on genome DNA amplification with subsequent electrophoretic separation=detection of multiple STR loci using complex and expensive CE devices.…”
mentioning
confidence: 99%